NONWOVEN DEVELOPMENT BY THE MULTILAYER STRUCTURE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The main two directives of the European Commission (EC) has been regulating the automotive industry. The aforementioned directives and education of residents on environmental issues has created the need for new materials that have been produced from renewable resources and should be recycled at the end of product life cycle.The objective of this project is to develop a nonwoven materials (NWM) that would incorporate fibers of plants, which could be grown in Latvia because of suitable local climate conditions, for the use in automotive industry. Furthermore, inclusion of polymer fibers in the NWM will expand the areas of use of such material – the NWM can be transformed into a composite material by means of a thermal press.Manufacturing process of NWM consist of structure modelling and material samples manufacturing. NWM samples production process to be carried out by fibers preparation, fibers mixing, formation by airlaid method, preparation of fiber webs for fixation with a mechanical needle punching method, mechanical fixation of fiber webs, preparation of fixed fiber webs for NWM manufacturing and manufacturing of NWM by mechanical needle punching method.This article reflects the comparison of two compositions NMW (Polylactid (PLA) (60 wt%) and long flax fibres (40 wt%), and PLA (60 wt%) and technical hemp fibres (40 wt%)) with the same structure by visual appearance, geometrical parameters and tensile strength. The average surface density of hemp NWM varies in the range of 792.09 to 958,71 g•m−2 , thickness varies from 6.91 to 9.23 mm. Flax NWM average surface density is higher than hemp NWM and varies in range of 1,064 to 1,260 g•m−2, thickness of the material varies from 12.62 to 15.54 mm. For comparison, the surface density of NWM currently used in automotive industry, depending on the use of the material, varies from 100 to 1,400 g•m−2.